A growing understanding of the role of muscarinic receptors in the molecular pathology and treatment of schizophrenia - Dean, Brian; Bakker, Geor; Ueda, Hiroki R.; Tobin, Andrew B.; Brown, Alastair; Kanaan, Richard A. A. (Frontiers in Cellular Neuroscience, 2023)
Pre-clinical models, postmortem and neuroimaging studies all support a role for muscarinic receptors in the molecular pathology of schizophrenia. From these data it was proposed that activation of the muscarinic M1 and / or M4 receptor would reduce the severity of the symptoms of schizophrenia. This hypothesis is now supported by results from two clinical trials which indicate that activating central muscarinic M1 and M4 receptors can reduce the severity of positive, negative and cognitive symptoms of the disorder. This review will provide an update on a growing body of evidence that argues the muscarinic M1 and M4 receptors have critical roles in CNS functions that are dysregulated by the pathophysiology of schizophrenia. This realization has been made possible, in part, by the growing ability to visualise and quantify muscarinic M1 and M4 receptors in the human CNS using molecular neuroimaging. We will discuss how these advances have provided evidence to support the notion that there is a sub-group of patients within the syndrome of schizophrenia that have a unique molecular pathology driven by a marked loss of muscarinic M1 receptors. This review is timely, as drugs targeting muscarinic receptors approach clinical use for the treatment of schizophrenia and here we outline the background biology that supported development of such drugs to treat the disorder.